Cultivar Mixtures in Bean Reduced Disease Infection and Increased Grain Yield Under Mountain Environment of Nepal - Prasad, R C; Paudel, M N; Ghimire, N H; Joshi, B K (Agronomy Journal of Nepal, 2016)
Field experiment on cultivar mixture was conducted for trailing type and bushy type bean (Phaseolusvulgaris L.) to know the effect of cultivar mixtures on grain yield and disease infection during summer season 2015 in Jumla. The result of the study revealed that agronomic attributes were enhanced while Anthracnose infection was reduced under cultivar mixtures of bean than those of their sole cropping both for trailing type and bushy type beans under study. Agronomy Journal of Nepal (Agron JN), Vol.4, Page: 128-135, 2016